Reliability and validity of the Turkish version of the WHO-5, in adults and older adults for its use in primary care settings. (2019) - Eser, Erhan; Çevik, Celalettin; Baydur, Hakan; Güneş, Soner; Esgin, Tayfun Alperen; Öztekin, Çağlar Söğüt; Eker, Esen; Gümüşsoy, Ufuk; Eser, Gün Baris; Özyurt, Beyhan
Abstract: Background: This study aims to determine the psychometric properties of the World Health Organization Well-Being Index (WHO-5) Turkish version in Turkish adults and older adults. Methods: This is a multicenter cultural adaptation study carried out with 1752 participants. Internal consistency (by Cronbach's alpha); Construct validity (by known groups and confirmatory factor analysis-CFI) and discriminant validity are evaluated stratified by adults and older adults. Cohen's Effect Size is used in known groups and discriminant validity analyses. Results: Distribution properties of the WHO-5 Turkish version are in acceptable limits. Alpha values are 0.81 for adults and 0.86 for older adults. The variances of the 58.5% of the adults sample and 63.9% of the older adults sample are explained in Exploratory FA. Model fits (CFI) are satisfactory ( > 0.95) in both samples; but RMSEA is poor in the older adults sample (0.166) whereas it is acceptable (0.073) in the adults sample. Known groups validity and discriminant analyses are satisfactory in both adults and older adults. Conclusion: The WHO-5 Turkish version has a good measurement capacity, internal consistency and good model fits in both samples. The error values in the older adults group suggest that the results when testing older adults should be interpreted with caution.